Nanowire reinforcement of woven composites for enhancing interlaminar fracture toughness. (January 2018) - Castellanos, AG; Islam, MS; Shuvo, MAI; Lin, Y; Prabhakar, P
A novel technique to improve the Mode I and Mode II interlaminar fracture toughness of woven carbon-fiber polymer matrix composite face sheets using zinc oxide nanowires is proposed. Zinc oxide nanowires are directionally synthesized on dry carbon fabrics that are used to manufacture the laminate. The influence of zinc oxide nanowires on interlaminar fracture toughness is compared against regular interfaces using double cantilever beam and end-notched flexure tests to provide fracture toughness values. A significant improvement in the Mode I and Mode II interlaminar fracture toughness values is observed with zinc oxide nanowires. Therefore, zinc oxide nanowire interlaminar reinforcement has been proven to enhance the interlaminar fracture toughness of textile composites.